2006
DOI: 10.1111/j.1083-6101.2003.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Gratification Niches of Monthly Print Magazines and the World Wide Web Among a Group of Special-Interest Magazine Subscribers

Abstract: Through the framework of niche theory, this study compared the gratification niches of monthly print magazines and the World Wide Web through a survey administered to 371 subscribers of a special‐interest magazine. The findings suggest that the Web offers a wider array of gratifications than magazines, and delivers them in a superior fashion. The Web excels among cognitive, task‐oriented uses; while magazines hold their ground for more affective, self‐oriented uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Theoretical models have attempted to offer some explanation into how humans skew their behaviour when allocating time to applications, channels, searches, or web pages. A key purpose of technology use is to keeping informed, enhance social interaction, as well as simple entertainment [22,30], and people use technology that they believe will offer the gratifications they seek [28]. Therefore, as a ubiquitously available solution, mobile phones naturally compete against other information sources for users' attention.…”
Section: User Characteristics or Preferences?mentioning
confidence: 99%
“…Theoretical models have attempted to offer some explanation into how humans skew their behaviour when allocating time to applications, channels, searches, or web pages. A key purpose of technology use is to keeping informed, enhance social interaction, as well as simple entertainment [22,30], and people use technology that they believe will offer the gratifications they seek [28]. Therefore, as a ubiquitously available solution, mobile phones naturally compete against other information sources for users' attention.…”
Section: User Characteristics or Preferences?mentioning
confidence: 99%
“…The niche theory, which developed originally from biology and evolution, has been widely used in media economics studies to examine the competition between mass media (e.g., Dimmick, Kline, & Stafford, 2000;Feaster, 2009;Randle, 2003). This theory holds that the concept of a niche does not necessarily denote a focused portion of the population, as suggested by phrases such as ''niche market.''…”
Section: The Theory Of the Niche: Communication Resources Niche Andmentioning
confidence: 99%
“…Thus, the two media competed over the gratification opportunities, which resulted to some extent in the displacement of traditional news media by the Internet. Similarly, Randle (2003) examined how print magazines and the web provided different gratification opportunities to their subscribers by comparing the two media's gratification niches. He found that the web is a superior medium, providing more gratifications, especially in the cognitive dimension.…”
Section: The Theory Of the Niche: Communication Resources Niche Andmentioning
confidence: 99%
“…Payne et al (1988) discovered that trade magazine readers were motivated by their environmental surveillance (information) and interaction needs. Other literature confirmed information as being the primary utility of B2B publications for the audience to do their work (Jeffers, 1989;Randle, 2003;Van der Wurff, 2002a, 2002b. B2B media service products such as advertising and events generate awareness, cause responses, enable transactions (Chamblee & Sandler, 1992;Fang, Huang & Palmatier, 2015), and establish business-to-business connections and interactions (Mair, 2013;Mair and Thompson, 2009;Medjahed, Benatallah, Bouguettaya, Ngu & Elmagarmid, 2003).…”
Section: Introductionmentioning
confidence: 97%